Second-Generation Antiandrogens: From Discovery to Standard of Care in Castration Resistant Prostate Cancer - Rice, Meghan A.; Malhotra, Sanjay V.; Stoyanova, Tanya (Frontiers in Oncology, 2019)
Prostate cancer is the most commonly diagnosed cancer affecting men in the United States. The prostate is a hormone-dependent gland in which androgen hormones testosterone and dihydrotestosterone bind to and activate the androgen receptor, initiating nuclear translocation of androgen receptor and a subsequent signaling cascade. Due to the androgen dependency of the prostate, androgen deprivation therapies have emerged as first line treatment for aggressive prostate cancer. Such therapies are effective until the point at which prostate cancer, through a variety of mechanisms including but not limited to generation of ligand-independent androgen receptor splice variants, or intratumoral androgen production, overcome hormone deprivation. These cancers are androgen ablation resistant, clinically termed castration resistant prostate cancer (CRPC) and remain incurable. First-generation antiandrogens established androgen receptor blockade as a therapeutic strategy, but these therapies do not completely block androgen receptor activity. Efficacy and potency have been improved by the development of second-generation antiandrogen therapies, which remain the standard of care for patients with CRPC. Three second-generation anti-androgens are currently approved by the Food and Drug Administration (FDA); enzalutamide, abiraterone acetate and recently approved apalutamide. This review is intended to provide a thorough overview of second-generation antiandrogen discovery, treatment application, strategies for combination therapy to overcome resistance, and an insight for the potential future approaches for therapeutic inhibition of androgen receptor.